SOSIALISASI PEMANFAATAN POTENSI SUMBER DAYA ALAM DALAM MENINGKATKAN EKONOMI DESA MELALUI INDUSTRI KECIL MENENGAH (IKM) DI DESA LAPPAE, KECAMATAN TELLU SIATTINGE, KABUPATEN BONE - Ilham, Ilham; Andi Gunawan; Andi Nur Fadillah; Fitri Ramadani; Dwiyani, Dwiyani; Andi Nurazizah A; A. Desi Vio Alvionita; Muh. Akbar; Sahrul Gunawan (Bajang Institute, 2024)
Small and medium industries (IKM) are business units that are classified as small and medium, playing an important role in a country's economy, especially in increasing employment opportunities, increasing people's income, and supporting local economic growth. Therefore, to increase the awareness of the Lappae Village community in increasing income, we held a seminar on the use of natural resources in improving the village economy through middle class industries (IKM). Based on the results of the implementation of activities, it is known that (1) the Lappae Village community has become more aware of the importance of utilizing the potential of local natural resources, (2) the community has gained knowledge and skills in developing small and medium businesses based on the village's natural potential